Racism in the 20th Century, Reflected through Nella Larsen’s Passing - Puspitasari, Anggi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
During the Jim Crow era, the artistic and literary movement known as the Harlem Renaissance emerged. Black writers and artists of the time voiced their concerns about racial discrimination and explored their identities and experiences through their work. Literature became a medium through which racial conditions in the 20th century were voiced. Therefore, this research aims to analyze how Nella Larsen’s Passing (1929) represents racism in America in the 20th century. This novel tells the story of two mixed-race women, Irene Redfield and Clare Kendry, who grew up together but took different paths in life. Irene embraces her African American identity, while Clare “passes” as white and lives in “white” society. To answer the research question, the researcher used Hall’s representation theory. Representation is a perspective in reading a text that connects meaning, language, and culture. In other words, representation is the production of meaning through language. Through language as a medium for conveying information, new ideas will be formed and communicated in ways that can be accepted and understood by other people. This research employs a descriptive qualitative approach with primary data from the novel and secondary data from books, theses, journals, articles, and online sources. The findings show Passing by Larsen illustrates the Jim Crow laws and internal racism that influenced the lives and choices of Black individuals in 20th-century America. This novel also portrays the dilemma faced by Black individuals in choosing between living under a system of segregation or trying to “pretend” to be white people to gain privileges. This research provides new insight into the complexities of 20th-century racism and its effects on the everyday lives of Black individuals.